Development and Validation of a Hydrophilic Interaction Liquid Chromatography Tandem Mass Spectrometry Method for the Determination of Asparagine in Human Serum - Haoyang Lu; Xiaoyun Zeng; Lihua Yu; Zhanzhang Wang; Danna Lin; Xiaojia Ni; Dewei Shang; Ming Zhang; Jinqing Hu; Shuhua Deng; Xiuqing Zhu; Yuqing Chen; et al. (International Journal of Analytical Chemistry)
L-Asparagine (ASN) is the catalyze substrate of L-asparaginase (ASNase), which is an important drug for acute lymphoblastic leukemia (ALL) patients. The ASN level is found to be closely associated with the effectiveness of ASNase treatment. In this study, a hydrophilic interaction liquid chromatography tandem mass spectrometry (HILIC-MS/MS) method was developed for the determination of ASN in the human serum using a stable isotope-labeled internal standard (ASN-D3). Serum samples were prepared by a one-step precipitation procedure using methanol and separated by an Agilent HILIC Plus column with the mobile phase of methanol-water (95 : 5, v/v, containing 5 mM ammonium formate and 0.1% formic acid), at a constant flow rate of 0.3 mL/min. Mass spectrometric analysis was conducted using multiple-reaction monitoring in the positive electrospray ionization mode. Serum ASN concentrations were determined over a linear calibration curve range of 2–200 μM, with acceptable accuracies and precisions. The validated HILIC-MS/MS method was successfully applied to the quantification of ASN levels in the serum from patients with ALL. Collectively, the research may shed new light on an alternative rapid, simple, and convenient quantitative method for determination of serum ASN in ALL patients treated with ASNase.